The Incidence and Characteristics of Venous Thromboembolisms in Paediatric-Onset Inflammatory Bowel Disease: A Prospective International Cohort Study Based on the PIBD-SETQuality Safety Registry. (2nd October 2021) - Aardoom, Martine A; Klomberg, Renz C W; Kemos, Polychronis; Ruemmele, Frank M; ,; van Ommen, C H (Heleen); de Ridder, Lissy; Croft, Nicholas M; ,
Abstract: Background and Aims: Guidelines regarding thromboprophylaxis for venous thromboembolisms [VTEs] in children with inflammatory bowel disease [IBD] are based on limited paediatric evidence. We aimed to prospectively assess the incidence of VTEs in paediatric-onset IBD [PIBD], characterize PIBD patients with a VTE and identify potential IBD-related risk factors. Methods: From October 2016 to September 2020, paediatric gastroenterologists prospectively replied to the international Safety Registry, monthly indicating whether they had observed a VTE case in a patient <19 years with IBD. IBD details [type, Paris classification, clinical and biochemical disease activity, treatment] and VTE details [type, location, treatment, outcome] were collected. To estimate VTE incidence, participants annually reported the number of PIBD patients, data source and catchment area of their centre. A systematic literature review and meta-analysis was performed to calculate the VTE incidence in the general paediatric population. Results: Participation of 129 PIBD centres resulted in coverage of 24 802 PIBD patients. Twenty cases of VTE were identified [30% Crohn's disease]. The incidence of VTEs was 3.72 (95% confidence interval [CI] 2.27–5.74) per 10 000 person-years, 14-fold higher than in the general paediatric population (0.27 [95% CI 0.18–0.38], p < 0.001). Cerebral sinus venous thrombosis was most frequently reported [50%]. All but one patient had active IBD, 45% were using steroids and 45% were hospitalized. No patient received thromboprophylaxis, whereas according to current PIBD guidelines, this was recommended in 4/20 patients. Conclusion: There is an increased risk of VTEs in the PIBD population compared to the general paediatric population. Awareness of VTE occurrence and prevention should be extended to all PIBD patients with active disease, especially those hospitalized. Graphical Abstract: